Effect of vitamin D supplementation on inflammatory status and behavioral symptoms in children with autism spectrum disorders: a double-blind randomized clinical trial - Zohreh Javadfar; Shahin Soltani; Firoozeh Khamoushi; Maryam Sharifi; Shima Moradi; Shahab Rezaeian; Ali Akbar Foroughi; Sahar Cheshmeh; Mehdi Taghaddosi; Fariborz Bahrehmand (BMC Pediatrics)
Abstract Purpose Inflammation in early childhood has been proposed as a clinically recognized risk factor for developing autism spectrum disorder (ASD). Since vitamin D has an anti-inflammatory role, this trial was aimed to evaluate the effects of vitamin D supplementation on TNF-α and IL-37 status and behavioral problems in children with ASD. Methods This parallel double-blind clinical trial study was conducted on 43 ASD children who were randomly allocated into two studied groups the vitamin D drop group received 300 IU/kg daily (n = 22) and, the control group (n = 21) for 15 weeks. Serum levels of 25(OH) D (ng/ml), and inflammatory indices including tumor necrosis factor-alpha (TNF-α) (ng/ml), and interleukin 37 (IL-37) (ng/ml) were measured at the start and end of the study. Moreover, the Real-Life Rating Scale for Autism (RLRS) questionnaire assessed behavioral symptoms. Results Of the participants, 55.6% in the intervention group and 44.4% in the control group were boys (P = 0.24). After 15 weeks of vitamin D supplementation, serum 25(OH) D levels significantly increased (P = 0.001), while TNF-α (P < 0.001) and IL-37 (P = 0.004) levels significantly decreased. The total RLRS score in the intervention group significantly decreased (P = 0.005), but no significant changes were observed in its subcategories (e.g., Sensory Motor Behaviors, Social Relationship to People) due to small, non-significant improvements accumulating to affect the total score. Between-group comparisons for RLRS were non-significant (P = 0.165). Conclusion The trial highlighted the possible anti-inflammatory role of vitamin D in children with ASD, as well as improving behavioral disorders. Level of evidence Level I- randomized controlled trial. Trial registration IRCT20170827035936N3, https://irct.behdasht.gov.ir/trial/27012 ; registration date: 16/09/2023.